DEEP SEISMIC REFLECTIVITY BENEATH AN INTRACRATONIC BASIN: INSIGHTS INTO THE BEHAVIOR OF THE UPPERMOST MANTLE BENEATH THE ILLINOIS BASIN - Okure M.S.; McBride J.H. (My University, 2006)
Reflectivity images of the lower crust and uppermost mantle beneath the Paleozoic Illinois basin have been derived from reprocessing of several hundred kilometers of industry seismic reflection data using extended vibroseis recorrelation. The recorrelation was based on extending an originally 4-s correlated record, acquired with a 16-s sweep, from 14 to 126 Hz, to the absolute limit of the full 20 s (~70 km) listening traveltime. Sub-Moho reflections are recorded to 18 s two-way traveltime (unmigrated) and are observed on intersecting profiles apparently dipping to the southwest and striking northwest-southeast. Occasional Moho reflections are also observed across the profiles (~12 s or ~38 km) while reflectivity in the lower crust is generally marked by intermittent horizontal packages and short, gently dipping reflections and diffraction segments. The presence of newly observed mantle reflectivity beneath the Illinois basin indicates significant uppermost mantle heterogeneity, relative to other parts of the USA studied using reflection methods. The mantle reflectivity effectively defines an area of anomalous mantle that rests beneath the depocenter of the early Paleozoic Illinois basin, which is itself superimposed over a deeper Proterozoic "basinal" depocenter. Filtering and inversion of geopotential field data reveal that this anomalous mantle also partially correlates with a positive density anomaly in the upper mantle. These correlations suggest that the anomalous mantle zone exerted an influence on the early Paleozoic subsidence of the basin, perhaps as a buried load due to eclogitization of former lower crust. The relatively isolated occurrence of sub-Moho reflections beneath the basin makes it difficult to uniquely infer their origin. However, available geologic and geophysical constraints, especially from geochemical and geochronological studies of drilled and exposed basement rocks, limit the possibilities to: (1) remnants or "scars" of sub-crustal processes associated with lithospheric extension or delamination related to the melting of the Proterozoic crust that led to the emplacement of the granite-rhyolite province that underlies much of USA Midcontinent; or (2) deformation caused by plate subduction associated with the hypothetical accretion of a juvenile island arc to the pre-1.6 Ga southern margin of the Laurentian continent. © 2006 Elsevier B.V. All rights reserved.
Keywords: MANTLE; PLATE TECTONICS; PROTEROZOIC; SEISMIC REFLECTION; Precambrian::Proterozoic; Докембрий::Протерозой